ASPERGILLUS FLAVUS MEDIATED SILVER NANOPARTICLES SYNTHESIS AND EVALUATION OF ITS ANTIMICROBIAL ACTIVITY AGAINST DIFFERENT HUMAN PATHOGENS - Wilson, A.; Prabukumar, S.; Sathishkumar, G.; Sivaramakrishnan, S. (International Journal of Applied Pharmaceutics, 2016)
Objective: Here, we report the extracellular synthesis of silver nanoparticles (AgNPs) using the cell-free extract of fungal isolate Aspergillus flavus and evaluation its inhibitory activity against bacterial pathogens. Methods: Synthesized AgNPs was characterized via high throughput instrumentation such as UVâ€“Visible spectrophotometer (UV-Vis) and Fourier transform infrared spectroscopy, High-resolution transmission electron microscopy (HRTEM), X-ray Diffraction (XRD) and Energy dispersive X-ray spectroscopy (EDAX). Results: Formation of yellowish brown colour clearly indicates the synthesis of AgNPs which produces a SPR peak at 420 nm. Active protein metabolites present in the cell-free extract plays a crucial role in reduction and stabilization of AgNPs. It was clearly observed that synthesized AgNPs were faced-centered cubic crystalline in nature with the mean size of 22Â±11 nm. Further, synthesized AgNPs capped with protein moieties exhibits excellent inhibitory activity against tested bacterial pathogens. Conclusion: In this study, we have isolated the fungal strain A. flavus from the infected larvae of D. eucharis from the soil. The active metabolites of isolated A. flavus have been successfully used as an eco-friendly reducing agent to generate AgNPs and synthesized particles can be potentially developed as a drug candidature for antimicrobial therapy.